2023
DOI: 10.3390/nano13061122
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tribological Performance of Low-Friction Nanocomposite WSexSy/NP-W Coatings Prepared by Reactive PLD

Abstract: A novel laser-based method for producing nanocomposite coatings consisting of a tungsten sulfoselenide (WSexSy) matrix and W nanoparticles (NP-W) was developed. Pulsed laser ablation of WSe2 was carried out in H2S gas under appropriate laser fluence and reactive gas pressure. It was found that moderate sulfur doping (S/Se ~0.2–0.3) leads to significant improvement in the tribological properties of WSexSy/NP-W coatings at room temperature. Changes in the coatings during tribotesting depended on the load on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Special Issue was focused on recent trends in the fabrication of functional nanostructures, nanomaterials and nanotextured surfaces using laser radiation. The resulting content of this Special Issue comprising 10 original papers reflects the diversity of the developing nanofabrication strategies that utilize pulsed laser radiation, including pulsed laser ablation in liquid (PLAL) for nanomaterial generation [ 1 , 2 , 3 , 4 ], pulsed laser deposition (PLD) of functional coatings [ 5 ], laser-induced forward transfer (LIFT) [ 6 ], laser sintering [ 7 ], pulsed laser surface nanotexturing [ 8 ] and direct laser writing in transparent media [ 9 , 10 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Special Issue was focused on recent trends in the fabrication of functional nanostructures, nanomaterials and nanotextured surfaces using laser radiation. The resulting content of this Special Issue comprising 10 original papers reflects the diversity of the developing nanofabrication strategies that utilize pulsed laser radiation, including pulsed laser ablation in liquid (PLAL) for nanomaterial generation [ 1 , 2 , 3 , 4 ], pulsed laser deposition (PLD) of functional coatings [ 5 ], laser-induced forward transfer (LIFT) [ 6 ], laser sintering [ 7 ], pulsed laser surface nanotexturing [ 8 ] and direct laser writing in transparent media [ 9 , 10 ].…”
mentioning
confidence: 99%
“…Importantly, the reported results bridge the gap between SERS-based bio-sensing and flexible electronics via inexpensive, scalable and environmentally friendly laser nanofabrication technology. Fominski et al reported the deposition of composite coatings made of a tungsten sulfoselenide (WSe x S y ) matrix embedding tungsten (W) nanoparticles through pulse laser ablation of WSe 2 carried out in gaseous H 2 S [ 5 ]. The PLD-fabricated coating demonstrated improved hardness and remarkable tribological characteristics even under multiple bending cycles and low temperature tests.…”
mentioning
confidence: 99%